Atmospheric Deposition of Multi-Class Substances into the Ocean: Synthesis of Fluxes, Seasonal Spatial Patterns and Ecological Risks - Qinghao Lin; Xianliang Yi; Junyi Wang; Yiwen Zhang; Jingjing Zhan (Journal of Marine Science and Engineering, 2026)
Atmospheric deposition is increasingly recognized as a significant pathway transporting diverse substances from land to the ocean. However, significant uncertainties persist regarding the magnitude, spatial variability, and ecological implications of these inputs into the ocean. This study compiles and standardizes observational datasets from published sources to provide a cross-substance synthesis of atmospheric concentrations, deposition fluxes, seasonal patterns, and ecological risks. The analysis covers major substance categories, including nutrients, trace metals, microplastics, POPs and other emerging pollutants. The novelty of this work lies in its cross-pollutant approach and the integration of seasonal dynamics, particularly for winter deposition. Global results show widespread deposition across the world’s oceans, with consistently elevated concentrations in densely populated coastal regions and detectable levels even in remote areas, underscoring the role of long-range transport. Our analysis reveals pronounced winter peaks in regions like the Bohai Sea and the Baltic Sea, highlighting a critical but often overlooked seasonal window. Strong nearshore-to-offshore gradients across most substances indicate dominant influences from coastal anthropogenic emissions. Ecological risk assessment using the Risk Quotient method suggests that risks are generally low but spatially heterogeneous, with hotspots in regions of intensive human activity. Overall, this synthesis highlights the importance of atmospheric pathways in shaping marine substance distributions and emphasizes the need for improved monitoring and modeling to better quantify episodic deposition processes under future environmental change.